EL MUNDO “NANO” DE ECUADOR, ¿CÓMO DE GRANDE ES - Gutiérrez Coronado, José L. (MOMENTO, 2018)
The state-of-the-art of nanotechnology and all its related areas is one of the most important due to its importance to know its scientific development in the different scientific disciplines and/or as future technological developments. In Latin America (LA) the increase in scientific publications, the association of networks and a greater presence of inventors are some of the features that show the growth of this "nano" area. In this scenario, this work tries to highlight, from the different "nano" meanings that are given as scientific lines in Ecuador, which is the general tendency observed in its research activities (56 universities) and will be compared with the countries of the environment, giving some general conclusions. In general, in Ecuador, in the last 4 years there has been a strong growth in impact publications but half of them are not mentioned and only slightly more than half are outside the country. On the other hand, as an example to follow in terms of patents, Costa Rica presents a benchmark for its rapid growth and momentum. Finally, the volume of graduate work is poor in relation to total production (1/4).